ANTI-FIBROTIC EFFECTS OF PROTEASOME INHIBITION ON BLEOMYCIN-INDUCED EXPERIMENTAL SCLERODERMA - Koca, S.; Ozgen, M.; Ozercan, I.; Dagli, F.; Ustundag, B.; Isi, A. (Clinical & Exper Rheumatology, 2010)
[Abstract Not Available]